2011
DOI: 10.1108/17579881111112421
|View full text |Cite
|
Sign up to set email alerts
|

ICT adoption and development: issues in rural accommodation

Abstract: Purpose -The work described in this paper is of direct relevance to those with an interest in the phenomena surrounding ICT (Information and Communication Technologies) adoption by the rural accommodation sector. The paper provides the results from a preliminary study, which examined differences in the level of inter-firm technology adoption between rural and urban accommodation establishments within a major tourism destination, Scotland. Design/methodology/approach -A survey was conducted, and the results set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In a comparative study, Reino et al (2011) found there were differences in inter-firm technology adoption in rural and urban accommodation establishments in Scotland. They use their study to theoretically explain different levels of adoption between the two settings.…”
Section: Corporate or Management Supportmentioning
confidence: 99%
“…In a comparative study, Reino et al (2011) found there were differences in inter-firm technology adoption in rural and urban accommodation establishments in Scotland. They use their study to theoretically explain different levels of adoption between the two settings.…”
Section: Corporate or Management Supportmentioning
confidence: 99%
“…), sometimes in cooperation with GIS, remote sensing and GPS technologies. The ICT technologies could find its applications also in social services like retail (e-commerce, e.g., Jalali et al (2011), hospitality service (e.g., Reino et al, 2011), health care (telemedicine, see e.g., Ruxwana, 2010), education or tourist information. It is seen from the citations that ICT is often applied in developing countries where physical accessibility is sometimes much more difficult than in developed countries.…”
Section: The Potential Of An Application Of the Smart Village Conceptmentioning
confidence: 99%
“…While many of the younger generations are technology savvy, the older generations living in rural areas may not be. Consistent with Reino and Frew (2011), the level of technology adoption is lower in rural accommodation establishments than those in urban areas. This may be because Langkawi hotels’ need for technology is not critical because although the cost of labour has increased it is still cheaper than the cost of purchasing new technology.…”
Section: Discussionmentioning
confidence: 62%